Sosialisasi Self-Healing Untuk Mengatasi Kecemasan Melalui Mindful Cooking Pada Mahasiswa Universitas Nurul Hasanah Kutacane - Siska Putri Belangi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Self-healing is healing that is called natural, because basically, humans are able to heal themselves in certain ways that are simple and comfortable. Self-healing therapy is a technique commonly used to overcome the anxiety a person feels. Some self-healing efforts include relaxation. Self-healing socialization activities to overcome anxiety through mindful cooking among Nurul Hasanah Kutacane University students were carried out among 30 Nurul Hasanah Kutacane University students from 16 December 2023 - 16 January 2024. Implementation of mindful cooking, starting from hearing, touch, sight, smell , and feelings, tasting the cooking ingredients one by one and activating all the senses. Also, in this phase, participants will receive an explanation of the definition of mindfulness and how mindful cooking impacts self-healing. The aim of this phase is for participants to understand mindful cooking and be able to apply it in everyday life. Participants seemed enthusiastic about the material presented by the presenters and were able to be actively involved, so that this outreach activity took place in a two-way system and many participants asked questions.